Effect of recombinant human erythropoietin on postoperative anemia in children and adolescents undergoing osteosarcoma and potential influencing factors: a single-center retrospective study - Liu, Lulu; Lin, Meili; Yang, Wenjun; Yao, Difei; Luo, Huan; Yu, Lingyan; Dai, Haibin (Frontiers in Pharmacology, 2025)
BackgroundRecombinant human erythropoietin (rhEPO) is an active glycoprotein secreted by the kidneys that improves anemia. The therapeutic role of rhEPO in anemia induced by surgical treatment after neoadjuvant chemotherapy in children and adolescents with osteosarcoma remains unclear. Additionally, factors influencing rhEPO efficacy in this context remain incompletely understood.ObjectiveThis study aimed to assess the efficacy of rhEPO in treating postoperative anemia in children and adolescents with osteosarcoma and identify the key factors that may influence the therapeutic outcomes of this patient population.MethodsThis retrospective study was conducted by pharmacists at a 4200-bed tertiary hospital in China, utilizing data extracted from the Hospital Information System. The study included patients aged 20 years or younger who were diagnosed with osteosarcoma and who underwent surgical treatment at the Second Affiliated Hospital, Zhejiang University School of Medicine, following the completion of two cycles of neoadjuvant chemotherapy. Data were collected between 1 January 2014, and 31 December 2023. Patients were divided into two groups on the basis of whether they received rhEPO treatment perioperatively: a control group (n = 36) and a treatment group (n = 68). The outcome data from both groups were compared to evaluate the effectiveness of rhEPO treatment and to identify factors affecting outcomes in patients with postoperative anemia.ResultsThis study included 64 males and 40 females (1.6:1 ratio), with a median age of 13 years and 2 months. Baseline anemia was present in 92.31% of patients (mild: 56, moderate: 40). Multiple linear regression analysis revealed that the use of rhEPO was significantly positively associated with length of hospital stay (B = 3.459, SE = 0.200, P = 0.005). Specifically, this result indicates that patients who received EPO had a mean length of hospital stay that was 3.459 days longer than that of patients who did not receive EPO. Univariate linear regression demonstrated that preoperative medication use independently predicted reduced hemoglobin concentrations on postoperative day 3 (OR = 6.75, 95% CI: 2.314 to 19.692, P < 0.001). Notably, Pearson correlation coefficients revealed a significant inverse relationship between total perioperative medication exposure and postoperative day 3 hemoglobin levels (r = −0.309, p = 0.007). Binary logistic regression analysis further indicated that preoperative medication use was independent predictors of outcomes in patients with postoperative anemia following osteosarcoma surgery.ConclusionFor hospitalized children and adolescents suffering from postoperative anemia following osteosarcoma surgery, rhEPO treatment can significantly shorten their hospital stay. Preoperative administration of rhEPO may be a key factor in rapidly helping patients to survive the postoperative hemoglobin trough. Given the inherent limitations of retrospective studies, further prospective research is warranted to validate these findings.